Investigating the testing effect: Retrieval as a characteristic of effective study strategies. (April 2019) - Bae, Christine L.; Therriault, David J.; Redifer, Jenni L.
Abstract: Presently, the most common approach to examining the testing effect is using a free recall form of retrieval practice. In this experiment, we compared free recall to other retrieval-based study strategies including practice quizzing, test-generation, and keyword. We also examined the possible benefit of coupling these retrieval-based strategies with free recall. A total of 338 undergraduates were randomly assigned to one of the nine conditions: a repeated retrieval (study-test) learning condition paired with one of the four retrieval-based strategies, a single retrieval (study-study) learning condition paired with a retrieval-based strategy, or a rehearsal (study-study-study) condition. Following a 7-day delay, students completed a test assessing retention of information learned. There was a significant interaction between learning condition (repeated vs. single retrieval practice) and type of retrieval-based strategy. Free recall and practice quizzing were the most effective types of retrieval practice, and coupling testgeneration and practice quizzing with free recall led to significant benefits in performance. Highlights: There was a significant interaction between learning condition and retrieval strategy type. In addition to free recall, practice quizzing was also linked to long-term information retention. Coupling practice quizzing and test-generation strategies with free recall benefited memory.